Partial oral antibiotic treatment of endocarditis in patients who inject drugs: a case series - Miller, Kaylie; Evans, Emily; Sheridan, Kathleen R.; Nauriyal, Varidhi; Viehman, J. Alexander; Rivosecchi, Ryan; Stoner, Bobbi Jo; El-Dalati, Sami (JAC-antimicrobial resistance, 2022)
Abstract Background Recent literature has demonstrated that partial oral antibiotic treatment of infectious endocarditis is non-inferior to IV therapy in select patients. Despite the rising incidence of injection drug use-related endocarditis, partial oral therapy has not been well studied in persons who inject drugs. Objectives To evaluate the rate of relapsed infection and 90 day mortality in patients with infectious endocarditis treated with partial oral antibiotic therapy. Methods Consecutive patients with infectious endocarditis treated with partial oral antibiotic therapy were identified by study investigators and reviewed by independent clinicians. The decision to use partial oral antibiotic therapy was made by the institution’s multidisciplinary endocarditis team. Results In 11 cases of infective endocarditis treated with partial oral antibiotic therapy, 9 of which were complicated by injection drug use, there were no relapsed infections with the primary organism. Five patients underwent surgical valve replacement, and the median duration of oral antibiotic therapy was 23 days. All patients survived to in-hospital discharge and 90 days post-discharge. Ten patients followed up with an infectious diseases provider after discharge. Conclusions These data add to existing literature demonstrating non-inferior outcomes with partial oral antibiotic treatment when compared with IV antibiotic treatment alone in patients with endocarditis, including persons who inject drugs.